Narrative Review of Web-based Healthy Lifestyle Interventions for Cancer Survivors - Williams, Victoria (Ann Rev Res, 2020)
This narrative review of web-delivered weight management, diet quality, and physical activity interventions for cancer survivors relies on a systematic search of PubMed, Psych Info, and EBSCOhost which identified 19 unique web-delivered lifestyle interventions for cancer survivors. The sample sizes for these studies ranged from 11–492. Intervention duration ranged from 1–12 months; however, most interventions were 6–12 weeks in length. Ten studies were randomized controlled trials (RCTs), two were two-arm quasi RCTs, and seven employed a single-arm pre/post-test design. Many (N= 15) of the interventions were well-grounded in behavioral theory, which may have led to favorable behavior change. Most studies (15-of-19) targeted and reported increases in physical activity, while only a few targeted and reported improvements in diet quality (36.9% and 15.8%, respectively) and weight management (26.3% and 10.5%, respectively). A notable limitation was that most studies were conducted among populations that were primarily White and female. Future directions for Internet-based lifestyle interventions for cancer survivors include increasing: (a) focus on multiple behavior change, (b) representation of male and minority populations to improve generalizability of findings, (c) extended intervention duration and follow-up to evaluate long-term efficacy of web-based lifestyle interventions, and (d) sample size to allow for adequate statistical power.